AKIBAT HUKUM TRANSAKSI PERJANJIAN SEWA MENYEWA ATAS DASAR KEPERCAYAAN KEPADA TEMAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI PANGKALPINANG NO. 36/PDT.G/2020/PN.PGP) - Hanseen Hanseen (Fakultas Hukum Universitas Tarumanagara, 2021)
In the implementation of leasing land and buildings, of course, it cannot be separated from risks or problems that occur that are not in accordance with the agreement letter that has been agreed between the lessee and the lessor. The formulation of the problem in this thesis is how the legality of the lease deed signed by a legal subject who does not have the authority to act on behalf of a second business entity, what are the legal consequences of the act of signing the lease deed by a legal subject who does not have the authority to act? represent a business entity. This research includes a normative research typology. Collecting data obtained through interviews with the defendants, lawyers and academics and in the study of literature or appropriate documents, then presented descriptively and analyzed qualitatively. The analysis was carried out with a juridical-normative approach. This thesis aims to provide an understanding to tenants regarding legal remedies for dispute resolution in land lease agreements on the basis of trust in friends and to provide an understanding of what steps can be taken to obtain their rights as owners. Based on the provisions of Article 1320 of the Civil Code.